Tear Trough and Lid–Cheek Junction Anatomy: Current Understanding and Nonsurgical Treatment - Liew, Steven; De Silva, Dinuksha (Facial Plastic Surgery, 2022)
The tear trough and lower eyelid are sentinel sites of facial aging and are increasingly the target of nonsurgical aesthetic procedures. This article will review the advances that have led to our current understanding of tear trough anatomy. We propose a new functional classification of the lid–cheek junction for soft tissue filler treatment, and suggest simpler stratification of patients seeking lower eyelid treatment based on the etiology of their tear trough depression. We aim to describe a stepwise approach to management, with specific technical considerations targeting the underlying causes of lower eyelid pathology. The common complications and pitfalls of nonsurgical tear trough management will be discussed.
Keywords: tear trough; lower eyelid; facial rejuvenation; hyaluronic acid filler; lid–cheek junction anatomy